النظرية السوسيولوجية بين الواقع و المأمول: ميشال كروزيه نموذجا - عازم، كهينة; رميشي ربيعة (University Of Eloued جامعة الوادي, 2022)
تلعب النظرية دورا أساسيا في تنمية العلوم و البحوث العلمية فهي المصدر الأساسي للباحثين و المنظرين، لأنها تساعد في توحيد و توضيح ما يتم التأكيد عليه حول الواقع المدروس. و تمنح الانسجام للميدان المعرفي بفضل ما تقترحه من تفسيرات التي يحتمل أن تظل محل اختبار دائم محك الوقائع و الأحداث. و كما تقوم على تسهيل الاتصال فيما بين الباحث و موضوعه، و بالتالي يهدف بحثنا إلى بيان مدى مساهمة النظرية الاجتماعية في بناء البحث العلمي و فهم الحياة الاجتماعية انطلاقا من المقاربات السوسيولوجية المتعددة، و من بين النظريات المساهمة في علم الاجتماع التنظيم و العمل نجد نظرية التحليل الاستراتيجي » لميشال كروزيه « لفهم واقع المنظمات و تأثيرها على المجتمع Abstract : Theory plays an essential role in the development of science and scientifique research. It is the primary source of researchers and theorists, because it helps to consolidate and clarify what is emphasized about the studied. Harmony is granted to the field of knowledge through the explanations it proposes, which are likely to remain a constant test of facts and events. As it facilitates communication between the researcher and his subject, our research therefore aims to show the extent to which social theory contributes to the building of scientific research and the understanding of social life based on multiple sociological approaches. Among the theories contributing to sociology are organization and work, the theory of strategic analysis by “Michel Crozier” to understand the reality of organizations and their impact on society.
مداخلة
Keywords: النظرية الاجتماعية; نظرية التحليل الاستراتيجي; مفهوم نسق الفعل الملموس; مناطق الارتياب; السلطة; social theory – theory of strategic analysis – concept of concrete action pattern – regions of suspicion – power; social theory; theory of strategic analysis; concept of concrete action pattern; regions of suspicion; power